Improved design of an advanced Ice Giants Net Flux Radiometer - Aslam, S; Calcutt, SB; Hewagama, T; Irwin, PG; Nixon, C; Quilligan, G; Roos-Serote, MC; Villanueva, G (Springer, 2024)
In this paper, the improved design of an Ice Giants Net Flux Radiometer (IG-NFR), for inclusion as a payload on a future Uranus probe mission, is given. IG-NFR will measure the net radiation flux, in seven spectral bands, each with a 10° Field-Of-View (FOV) and in five viewing angles as a function of altitude. Net flux measurements within spectral filter bands, ranging from solar to far-infrared, will help derive radiative heating and cooling profiles, and will significantly contribute to our understanding of the planet’s atmospheric heat balance and structure, tropospheric 3-D flow, and compositions and opacities of the cloud layers. The IG-NFR uses an array of non-imaging Winston cones integrated to a matched thermopile detector Focal Plane Assembly (FPA), with individual bandpass filters and windows, housed in a vacuum micro-vessel. The FPA thermopile detector signals are read out in parallel mode, amplified and processed by a multi-channel digitizer application specific integrated circuit (MCD ASIC) under field programmable gate array (FPGA) control. The vacuum micro-vessel rotates providing chopping between FOV’s of upward and downward radiation fluxes. This unique design allows for small net flux measurements in the presence of large ambient fluxes and rapidly changing temperatures during the probe descent to ≥10 bar pressure.